Long-term Exercise After Pulmonary Rehabilitation (LEAP): a pilot randomised controlled trial of Tai Chi in COPD. Issue 3 (12th July 2021) - Moy, Marilyn L.; Wayne, Peter M.; Litrownik, Daniel; Beach, Douglas; Klings, Elizabeth S.; Davis, Roger B.; Pinheiro, Adlin; Yeh, Gloria Y.
Mind–body modalities are promising strategies to maintain the benefits gained after completion of conventional pulmonary rehabilitation in persons with COPD. In this pilot randomised controlled study we examined Tai Chi in persons with COPD after completing pulmonary rehabilitation. Participants were randomised 2:2:1 to Tai Chi (TC), usual care (UC) or group walking (GW) for 24 weeks. We assessed feasibility; primary outcome was exercise capacity measured by 6-min walk test (6MWT) distance at 24 weeks. Secondary outcomes included health-related quality of life measured by Chronic Respiratory Questionnaire (CRQ), dyspnoea, mood, stress, social support, self-efficacy, physical activity and exercise engagement. Effect size estimates and estimates from generalised estimating equations were calculated. Ninety-one persons (36 TC, 37 UC, 18 GW) were enrolled, with mean age 69±6 years, 59% male, and forced expiratory volume in 1 s % predicted (FEV1 % pred) 48±19%. There was no difference in adherence and adverse events between groups. There was a small between-group effect size (ES=0.25) in change in 6MWT distance favouring TC compared to UC; 24-week comparison was nonsignificant (p=0.10). There were no differences in secondary outcomes. In exploratory analyses, there was a greater percentage of participants in TC who improved 6MWT distance at 24 weeks, compared to UC, 64% versus 39%, p=0.05. There were higher percentages of participants in TC who improved CRQ Fatigue (59% versus 31%, p=0.02) and CRQ Mastery (47% versus 20%, p=0.01) domain scores, compared to UC. For GW, there were no differences compared with TC. Tai Chi may be a feasible option to maintain the benefits gained after completing conventional pulmonary rehabilitation. Tai Chi, a mind–body modality, may be a feasible option to maintain the benefits gained in exercise capacity and health-related quality of life after completion of outpatient conventional pulmonary rehabilitation https://bit.ly/32YI7Zp